2022
DOI: 10.1002/lt.26429
|View full text |Cite
|
Sign up to set email alerts
|

Complete transition from open surgery to laparoscopy: 8‐year experience with more than 500 laparoscopic living donor hepatectomies

Abstract: This study was designed to review laparoscopic living donor liver transplantations (LDLTs) at a single center that achieved complete transition from open surgery to laparoscopy. LDLTs performed from January 2013 to July 2021 were reviewed. Comparisons between open and laparoscopic surgeries were performed according to periods divided into initial, transition, and complete transition periods. A total of 775 LDLTs, 506 laparoscopic and 269 open cases, were performed. Complete transition was achieved in 2020. Bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…At our center, we have been using an ITM of 400 μg for open donor hepatectomy since 2007. However, our center started laparoscopic donor hepatectomy in 2013 and completely transitioned from open to laparoscopic donor hepatectomy in 2020 9 . Laparoscopic donor hepatectomy has been demonstrated to produce similar surgical outcomes to those of the open approach, but with less postoperative pain and faster hospital discharge 10,18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At our center, we have been using an ITM of 400 μg for open donor hepatectomy since 2007. However, our center started laparoscopic donor hepatectomy in 2013 and completely transitioned from open to laparoscopic donor hepatectomy in 2020 9 . Laparoscopic donor hepatectomy has been demonstrated to produce similar surgical outcomes to those of the open approach, but with less postoperative pain and faster hospital discharge 10,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Although ITM has been shown to provide effective postoperative analgesia up to 24–30 h after surgery, the high frequency of side effects such as postoperative nausea and vomiting (PONV), pruritus, and potential delayed respiratory depression have been significant drawbacks in the early recovery of living donors 3,5 . Moreover, a dose of 400 μg ITM was established based on open laparotomy; however, in 2020, our center completely transitioned from open surgery to laparoscopic surgery in living liver donors 9 . Since one of the benefits of laparoscopic surgery is less postoperative pain compared to open hepatectomy, it is suggested that ITM administration dosing guidelines must be adjusted appropriately as surgical procedures change to minimally invasive techniques 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our initial study revealed that ABOi LDLT can be performed safely with outcomes similar to those of ABOc LDLT. 5,8–10 However, our more recent study showed that ABOi LDLT was associated with poor graft survival compared with ABOc LDLT 11 …”
Section: Introductionmentioning
confidence: 95%
“…[5,[8][9][10] However, our more recent study showed that ABOi LDLT was associated with poor graft survival compared with ABOc LDLT. [11] In recent years, there have been reports that ABOi LDLT is related to antibody-mediated rejection and biliary complications, particularly ischemic-type diffuse biliary stricture. [2,12] A review of our data on ABOi LDLT revealed that this type of biliary complication occurred predominantly in patients who received liver grafts from donors with a laparoscopic donor hepatectomy.…”
Section: Introductionmentioning
confidence: 99%